Improvement of nutritional value of cocoa pod husk fermented with Aspergillus Spp. and two levels of urea and ammonium sulphate - Susana IW Rakhmani; T Purwadaria (Indonesian Center for Animal Research and Development (ICARD), 2017)
Cocoa pod husk is abundant as a waste product of cocoa plantation and potential as feed ingredient but has low nutritional value. To increase the nutritive value of cocoa pod husk (CPH), biological process through solid substrate fermentation using Aspergillus oryzae and Aspergillus niger and addition of two doses (N1 and N2) of nitrogen mixture had been done. The product is Fermented Cocoa Pod Husk (FCPH). Protein content increased from 50 g/kg before fermentation to 133.8 g. kg-1 for N1 for A. niger and 150 g/kg using A. oryzae. True protein were 99.8 and 93.5 g/kg for N1 and N2 treatments (A. niger); 119 and 104.1 g/kg for N1 and N2 treatments (A. oryzae). Aspergillus niger showed a superiority in term of enzymes production when compared to Aspergillus oryzae. Mannanase activy in A. niger fermentation product with N1 dose reached up to 2654 U/g and A.oryzae was 1122 U/g. Dry matter and protein digestibility for A. niger FCPH were 47 and 57% and A. oryzae FCPH were 52 and 62% repectively. Fermentation processed of CPH yield a product that very potential as an alternative feed with higher in protein content and contain mannanase enzyme.